2021
DOI: 10.1002/anie.202012921
|View full text |Cite
|
Sign up to set email alerts
|

Silver in the Center Enhances Room‐Temperature Phosphorescence of a Platinum Sub‐nanocluster by 18 Times

Abstract: There has been controversy surrounding the roles of the metal core (metal–metal interaction) and the shell (metal–ligand interaction) in photoluminescence of ligand‐protected metal nanoclusters. We have discovered aggregation‐induced room‐temperature phosphorescence of a platinum–thiolate complex and its silver ion inclusion complex (a silver‐doped platinum sub‐nanocluster). The inclusion of silver ion boosted the photoluminescent quantum yield by 18 times. Photophysical measurements indicate that the rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…This "central lock-atom" strategy for the suppression of non-radiative transitions and the enhancement of PL is different from the previous strategy for the PL enhancement of gold nanoclusters which is based on surface engineering. [9,11,38,39] It should be noted that very recently, Yamamoto et al [40] reported that the central Ag atom could enhance the phosphorescence of platinum nanoclusters.…”
Section: Resultsmentioning
confidence: 99%
“…This "central lock-atom" strategy for the suppression of non-radiative transitions and the enhancement of PL is different from the previous strategy for the PL enhancement of gold nanoclusters which is based on surface engineering. [9,11,38,39] It should be noted that very recently, Yamamoto et al [40] reported that the central Ag atom could enhance the phosphorescence of platinum nanoclusters.…”
Section: Resultsmentioning
confidence: 99%
“…These considerations are even more dramatic when two different metal precursors are engaged, rendering the rational preparation of heterobimetallic entities extremely challenging. Postmodification strategies, such as doping of monometallic clusters with heterometal atoms, or rearrangement of two independently synthesized monometallic clusters, are emerging approaches that have attracted substantial interest recently, but so far are limited to thiolate or carbonyl metal clusters. Lability phenomena and metal exchange strategies in polyhydride metal clusters are much less investigated to date.…”
Section: Introductionmentioning
confidence: 99%
“…Metal cluster with atom precision is an important class of nanomaterial and has become an emerging field in recent years. Because of their well-defined structures and unique physicochemical properties, metal clusters can be regarded as an ideal platform and provide an excellent opportunity to study the relationship between structure and property, thereby triggering widespread research enthusiasm from the academic community. Doping with heteroatom(s) is an effective strategy to manipulate the structure and property of metal clusters. Compared with monometallic clusters, bimetallic clusters are more attractive for practical applications due to the significantly improved physicochemical properties induced by the synergistic effect. Nowadays, great efforts have been made in doping gold clusters with group IB element (Ag or Cu), while less work has been conducted on doping with group IIB metals such as Cd. The pioneer contribution of Cd-doped bimetallic clusters was demonstrated respectively by Wang et al and Yao et al in 2015. Using Au 25 (SR) 18 as a template for doping, they used one Cd atom to replace a Au atom at either the center or vertex of the icosahedral Au 13 core by slight regulating the reaction conditions. , From then on, more efforts have been devoted to fabricating Cd-doped metal clusters; importantly, the structure features and the intriguing properties of those clusters have been revealed. For instance, Jin and co-workers reported the synthesis of [Au 19 Cd 2 (SR) 16 ] − cluster by tailoring the surface of [Au 23 (SR) 16 ] − via Cd doping, and the single-crystal X-ray analysis shows that the core of [Au 19 Cd 2 (SR) 16 ] − is identical to that of [Au 23 (SR) 16 ] − , while their surface structures are distinct .…”
Section: Introductionmentioning
confidence: 99%